ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN MATERI BANGUN RUANG - Eka Trisnawati; Nina Riana (Hipotenusa Journal of Research Mathematics Education (HJRME), 2018)
Mathematical communication skills that need to be developed through learning so that students are able to communicate ideas, thoughts, or opinions in learning mathematics. considering the importance of mathematical communication skills, a teacher should be able to build students' mathematical communication skills. Through mathematical communication students can express their understanding both orally and in writing, while students who have low learning abilities will find it difficult to achieve good learning outcomes. This study aims to: (1) determine the percentage of students' abilities in solving geometrical problems, (2) find out the causes of students' difficulties in solving geometrical problems, (3) find out how to overcome students' difficulties in solving spatial problems. . In this research, the method used is descriptive qualitative method. The population in this study were students of class VIII SMP Negeri 5 Bandar Lampung with a total of 187 students and took 30 students as research samples. Based on the results of the study, it can be obtained: (1) students who are able to solve geometrical problems are 62.99% and those who have difficulty are 37.01%, (2) the causes of students experiencing difficulties in solving spatial problems are: students do not understand the concept of space in applying to a question, students are not careful in working on every question that exists, (3) how to overcome student difficulties, namely: increasing students' ability to understand the concept of building space by giving emphasis when delivering material, doing more in the form of evaluation exercises. exercises at the end of each learning activity, and giving homework to finalize the material that has been delivered and shows that the indicators of mathematical communication are writing (writing), drawing (drawing), mathematical expressions (expression mathematic). The indicator with the highest percentage is writing (writing) and the indicator with the lowest percentage is mathematical expression (mathematical expression) this is because students have difficulty expressing mathematics in the form of symbols.